Efektivitas Model Pembelajaran Scramble pada Keterampilan Menulis Kalimat Siswa Kelas III SDN Pabuaran Tumpeng 2 Kota Tangerang - Rahayu, Isti Setia; Nurhayati, Siti; Manik, Nelly (MASALIQ, 2021)
Learning Indonesian Language and Literature in schools is to develop language skills both orally and in writing. Most students find it difficult to develop aspects of writing. Especially in stringing words to be arranged into a sentence. This difficulty may be caused by teachers who in their delivery are less precise and almost never use appropriate media. The problems mentioned above require alternative solutions in the form of learning models that can improve students' writing skills. A model that can provide a lot of information to students in order to inspire students and improve writing skills, through the Scramble Learning Model, students can find information about various vocabularies. In this study, researchers used quantitative methods and the variety of methods used in this study was experimental research with a pre-experimental design type of experiment. The research design used was a one-group pre-test-post test. Then the data collection technique used in this research is to use test questions (pre test and post test), observation, interviews and documentation. The research analysis uses the arithmetic mean. Based on the results of the post-test hypothesis, the t-test with the results of the T-value > with the T-table value, so that Ha which means 'Effectiveness of the Scramble Learning Model on Sentence Writing Skills for Class III Students at SDN Pabuaran Tumpeng 2 Tangerang City is accepted, and Ho which means "No Effectiveness". The Scramble learning model on Sentence Writing Skills for Class III Students at SDN Pabuaran Tumpeng 2 Tangerang City was rejected.